2018
DOI: 10.3233/xst-180391
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective study of SPECT/CT scans using SUV measurement of the normal pelvis with Tc-99m methylene diphosphonate

Abstract: Determination of the SUV value of the normal pelvis with 99m Tc-MDP SPECT/CT is feasible and highly reproducible. SUVs of the normal pelvis showed a relatively large variability. As a quantitative imaging biomarker, SUVs might require standardization with adequate reference data for the participant to minimize variability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 23 publications
(13 reference statements)
1
11
2
Order By: Relevance
“…Bone mineral density (BMD) obtained through dual X-ray absorptiometry (DEXA) is the gold standard and previous studies showed a significant positive correlation between HU and BMD [23] [24]. By analyzing the correlation between CT value and SUV, we found that SUVmax of each vertebral segment had a negatively strong correlation with the CT value (HU), which is contrary to the results of previous studies [20][25] [26],those only analyzed the relationship between SUVmax and CT value of lumbar vertebrae while the gravity and blood supply of vertebral bodies were consistent. Different from previous studies, we analyzed the relationship between SUVmax and CT value of all vertebral body segments.SUVmax of 99mTc-MDP in bone is often associated with blood supply and bone mineral density [27].…”
Section: Discussioncontrasting
confidence: 77%
See 1 more Smart Citation
“…Bone mineral density (BMD) obtained through dual X-ray absorptiometry (DEXA) is the gold standard and previous studies showed a significant positive correlation between HU and BMD [23] [24]. By analyzing the correlation between CT value and SUV, we found that SUVmax of each vertebral segment had a negatively strong correlation with the CT value (HU), which is contrary to the results of previous studies [20][25] [26],those only analyzed the relationship between SUVmax and CT value of lumbar vertebrae while the gravity and blood supply of vertebral bodies were consistent. Different from previous studies, we analyzed the relationship between SUVmax and CT value of all vertebral body segments.SUVmax of 99mTc-MDP in bone is often associated with blood supply and bone mineral density [27].…”
Section: Discussioncontrasting
confidence: 77%
“…It has been reported that SUVmax of the vertebra and pelvis was independent of height, however, the results are controversial [29] [30] [11]. The opposite conclusions from these studies may due to the small sample size.…”
Section: Discussionmentioning
confidence: 97%
“…A bone scan is a type of nuclear medicine-based imaging that provides an entire skeletal visualization based on the activity of a radionuclide tracer within a short amount of time. Two of the most widely used bone scan instruments are gamma cameras and single-photon emission computed tomography (SPECT), both of which are used with 99m Tc-methylene diphosphonate (MDP) tracer [ 4 ]. Conventionally, the interpretation of bone scan images has been based on a qualitative approach alone, whereby the images produced are evaluated using relative intensity values rather than absolute tracer concentration values [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, few researchers have studied the measurement of SUV in SPECT/CT bone scans with 99m Tc tracers thus far [ 4 - 6 , 8 , 13 ]. Therefore, the chief purpose of this study is to report the SUV measured for the normal vertebrae of breast cancer patients undergoing 99m Tc-MDP bone scans via a SPECT/CT machine.…”
Section: Introductionmentioning
confidence: 99%
“…SUVs in the normal vertebrae did not show a significant correlation with subject's weight but with the height in a study 25 ; however, another research conveyed the opposite 24 . Regarding differences in SUVs by gender, previous studies also showed different results 25,26 .…”
Section: Discussionmentioning
confidence: 93%